Endoscopic botulinium toxin-A application in the treatment of obesity: The effect of dose and application area on treatment success (Annals of Medical Research, 2023)
Aim:  In this study, it was aimed to examine the effect of dose and region on the effectiveness of Endoscopic Botulinum toxin A application in the fight against obesity.Materials and Methods: A total of 446 patients who applied to our clinic with the complaint of weight were included in the study. Endoscopic Botulinum toxin A was administered at doses of 300 U (n=74), 400 U (n=172) and 500 U (n=200) according to the weight and Body Mass Index (BMI) values of the patients. Patients were divided into three groups in the Preploric, Cardia and Fundus regions, after 125 U of Endoscopic Botulinum toxin A application to each region, and 125 U application to one region.Results:  Initial BMI, weight difference, last BMI and BMI differences were statistically significant between patient groups according to dose and area (p=0.000). All BMI differences between paired dose and area groups were statistically significant (p=0.000). BMI difference was significantly correlated with gender (r=0.108; p=0.023), Initial BMI (r=0.266; p=0.000), weight (r=0.219; p=0.000), dose (r=0.834; p=0.000), and area (r=0.200; p=0.000). Effects of initial BMI (B=0.031; p=0.031), dose (B=1.423; p=0.000) and area (B=0.316; p=0.000) on BMI difference were statistically significant.Conclusion: Optimum results are obtained in the application of fundus region with a density of 500 U in total, but at levels or values below this, the results may not be effective. Weight loss with the Endoscopic Botulinium toxin-A method with the appropriate dose and area is an effective and usable method in the fight against obesity.
Keywords: Botulinium toxin-A; Obesity; Region; Dose